Struktur-, Effizienz- und Einkommenswirkungen von Direktzahlungen - Katrin Happe; Alfons Balmann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Structural Efficiency and Income Effects of Direct PaymentsThe paper analyses various forms of direct payments using the agent-based model AgriPoliS. The model is fitted to the agricultural region 'Hohenlohe' in Baden-Wur̈ttemberg which is characterised by intensive livestock farming. The policy simulations show that decoupled payments which are attached to land do not have significant effects on structural change, competitiveness, and income as compared to the current Agenda 2000 policy. In order to reach a significant and lasting effect on the competitiveness of agriculture direct payments would have to be granted independently of production, land use, and farming activity in general. In order to ensure a sufficient degree of land management, area payments should be decreased to an extent which is just necessary to maintain certain land management standards. In an agricultural region where most land is leased, such a policy would break with the effect that only a small fraction of the income payment stays with the tenant, but is transferred to the land owner. It is especially the farms with a growth potential and a high share of rented land that would benefit from such a policy. The final section of the paper discusses the results in the light of the used modelling approach and with respect to future policy formation.
Keywords: 330; Agrarsubvention; Agrarstruktur; Agrareinkommen; Effizienz; Wirkungsanalyse; Baden-Württemberg; Deutschland; Agentenbasierte Modellierung